Dispersal and genetic differentiation of Syntrichia caninervis populations across different desert regions in China. (3rd April 2019) - Yin, B.; Zhang, Y.; Zhang, T.; Lin, L.; Lou, A.
Abstract: The moss Syntrichia caninervis is widely distributed in cool temperate and cold deserts where environmental pressures create a dependence on asexual reproduction (fragment reproduction). However, when compared to sporophyte‐producing mosses, there is a lack of evidence to support the capacity of drought‐tolerant mosses that predominantly fragment and produce protonema to disperse over long distances. We used 20 microsatellite loci to study genetic variation and structure in six populations (five natural populations and one population from a regeneration site) in three contrasting and widely separated regions of China. The genetic diversity and expected heterozygosity were lower in populations from the Tengger Desert than in populations from the other regions. Using PCoA, UPGMA and Structure analysis, the genetic grouping divided the three regions into three distinct groups. This may indicate that in regions where S. caninervis reproduces predominantly asexually, propagules are spread mainly by short‐distance dispersal. The genetic diversity of the population from the regeneration site in the Tengger Desert was slightly higher than that of the nearby, naturally occurring population, and included some input from the Pamir Plateau almost 2, 300 km to the west, suggesting long‐distance dispersal of S. caninervis propagules across the region. Predominantly asexually reproducing populations of S. caninervis are mainly dependent on short‐distance dispersal. Long‐distance dispersal of S. caninervis propagules across the region is difficult. Establishment of populations with dominant asexual reproduction will eventually result in genetic differentiation.